Exploring the Impact of the Federal Tax Credit on the Plug-In Vehicle Market. Issue 1 (2016) - Tal, Gil; Nicholas, Michael
The effect of the federal Plug-In Electric Drive Vehicle Credit on plug-in electric vehicle (PEV) sales is assessed in the United States by using an ex post stated preference survey of more than 2, 882 PEV owners in 11 states. This study attributes more than 30% of the PEV sales to the federal tax credit, with an impact of up to 49% for the Nissan LEAF. The incentive shifts buyers from internal combustion engine vehicles to plug-in vehicles and advances the purchase timing of new vehicles by 1 year or more. The impact of the incentive on buyers of varying sociodemographic and vehicle choice characteristics is explored through the use of three performance measures, including number of vehicles sold, kilowatt-hours of capacity sold, and electric vehicle miles traveled per year. The results of this paper add to the discussion of the impact of monetary incentives on the alternative-fuel vehicle market and present possibilities for improving the performance of monetary incentives in the PEV market.